A COMPREHENSIVE TOOL FOR ASSESSING CREATIVE THINKING IN MATHEMATICS EDUCATION - Al Ashari, Iqbal Ma’ruf; Anwar, Lathiful; Sulandra, I Made (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
In education, creativity is viewed as a fundamental behaviour especially when it comes to mathematics where students are motivated to tackle problems in unique ways. The present study sought to design, construct and validate an instrument that would assess creativity in geometry by employing three aspects of creativity as proposed by the aforementioned model- fluency, flexibility and originality. The instrument was administered to 30 junior high school students in Malang Indonesian. In this study, the assessment of internal and external consistent validity and dimensional structure of the instrument using a combination of Cronbach’s Alpha, Exploratory Factor Analysis (EFA), and inter-rater reliability was done. The reliability estimates showed that across the 7-item test, a validation score of Cronbach’s Alpha at 0.857 was achieved. Item-Total Statistics indicated that most items possessed high item-total correlations except item Q3 which possessed low item-total corrected correlation. EFA resulted in the segregation of 2 components which accounted for 81.280% of the variance of the construct and were labeled as fluency/flexibility and originality. This finding is consistent with already existing theories in creativity areas which argue that creative thinking is a multi-faceted phenomenon. This needs elucidation in order to improve the validity of the affected test items especially those aimed at measuring the different dimensions of creativity. The research enriches the existing literature based on creativity in mathematics education considering the primary aim to develop a sound and valid tool for assessing students' creative problem solving abilities in geometry.